Quantification of Influences on Student Perceptions of Group Work - Butt, Adam (Journal of University Teaching and Learning Practice, 2018)
How students perceive group work is closely correlated with the benefits of group work experience. However, a great variety of influences affect student perceptions of group work. This study quantifies the impact of various influences on the effective working, learning assistance and enjoyment of group work. This is done by analysing 206 responses to a survey of students in a course in actuarial science. A mixed ordered logit model is used to explicitly quantify the effect of various exogenous and endogenous influences on perceptions of group work. Student perceptions of group work are most heavily influenced by course design decisions regarding the scaffolding provided to groups, the expectation about whether or not they will enjoy group work, and their role undertaken in the group, including their level of effort (but not quality) relative to other group members. Implications for teaching practice are discussed.